The knowledge corrupters: hidden consequences of the financial takeover of public life - Crouch, Colin (Cambridge, 2015)
"In principle the advanced, market–driven world in which we now live is fuelled by knowledge, information and transparency, but in practice the processes that produce this world systematically corrupt and denigrate knowledge: this is the powerful and provocative argument advanced by Colin Crouch in his latest exploration of societies on the road to post–democracy.